Covalent-architected molybdenum disulfide arrays on Ti3C2Tx MXene fiber towards robust capacitive energy storage. (10th March 2023) - Sun, Suya; Zhu, Xiaolin; Wu, Xingjiang; Xu, Meigui; Hu, Ying; Bao, Ningzhong; Wu, Guan
Highlights: Use microfluidic and micro-reaction strategy to fabricate MoS2 -Ti3 C2 T x fibers. The vertically-aligned MoS2 can provide abundant diffusion paths for ion storage. The covalent engineering can facilitate rapidly interfacial electron conduction. The MoS2 -Ti3 C2 T x fiber has high energy density and superior durability. The as-prepared F-SC can realize stable energy supply for wearable electronics. Abstract: Ti3 C2 T x MXene fiber has shown extraordinary potential for supercapacitor electrode in wearable electronics and textile energy storage, but realizing high energy density and practical-powered applications remains a great challenge. Here, we report a covalent-architected molybdenum disulfide-Ti3 C2 T x (MoS2 -Ti3 C2 T x ) core-shell fiber for high-performance supercapacitor. Benefiting from the microfluidic and micro-reaction strategies, the ordered MoS2 arrays are strongly bridged on Ti3 C2 T x fiber via Ti-O-Mo bond, resulting in large exposed surface, enhanced porosity and excellent interfacial conduction for charges high diffusion and faradaic transfer. The MoS2 -Ti3 C2 T x fiber exhibits ultra-large capacitance of 2028 F cm −3 and admirable reversibility in 1 M H2 SO4 aqueous electrolyte. Meanwhile, MoS2 -Ti3 C2 T x fiber-based solid-state supercapacitor presents high energy density of 23.86 mWh cm −3, capacitance of 1073.6 F cm −3 and superior cycling ability of 92.13% retention after 20, 000 cycles, which can realize stable energy supply for wearable watch, LEDs, electric fans, toy ship and self-powered devices. Our work may provide an insightful guidance for the advanced design of structural fiber towards robust new energy and next-generation wearable industry. Graphical abstract: We develop an interfacial-ordered engineering of covalently tailored MoS2 -Ti3 C2 T x core-shell fiber via microfluidic spinning and micro-reaction strategy, where the shell layer of MoS2 arrays is in - situ coupled into the core layer of Ti3 C2 T x fiber by Ti-O-Mo bonds. The MoS2 -Ti3 C2 T x fiber-based F-SC delivers superior electrochemical performance, such as high energy density and admirable reversibility, realizing the energy supply and self-powered applications. Image, graphical abstract